The Potential of Ultrasonic Membrane Anaerobic System (UMAS) in Treating Slaughterhouse Wastewater - Nour, A. H.; R. M., Yunus; Azhari, H. Nour (Asian Research Publishing Network (ARPN), 2016)
In the wake of energy crisis and the drive to reduce CO2 emissions, the alternative energy sources are much demanded in order to reduce energy consumption, to meet legal requirements on emissions, and for cost reduction and increased quality. The direct discharge of slaughterhouse wastewater causes serious environmental pollution due to its high chemical oxygen demand (COD), Total suspended solids (TSS) and biochemical oxygen demand (BOD). The conventional ways for slaughterhouse wastewater treatment have both economic and environmental disadvantages. In this study, ultrasonic assisted- membrane anaerobic system (UMAS) was used as an alternative, cost effective method for treating slaughterhouse wastewater. Six steady states were conducted as a part of a kinetic study that considered concentration ranges of 7,800 to 13,620 mg/l for mixed liquor suspended solids (MLSS) and 5,359 to 11,424 mg/l for mixed liquor volatile suspended solids (MLVSS). Kinetic equations from Monod, Contois and Chen & Hashimoto were employed to describe the kinetics of slaughterhouse treatment at organic loading rates ranging from 3 to 11 kg COD/m3/d. The removal efficiency of COD during the experiment was from 94.8 to 96.5% with hydraulic retention time, HRT from 308.6 to 8.7 days. The growth yield coefficient, Y was found to be 0.52gVSS/g COD the specific microorganism decay rate was 0.21 d-1 and the methane gas yield production rate was between 0.24 l/g COD/d and 0.56 l/g COD/d. Steady state influent COD concentrations increased from 16,560 mg/l in the first steady state to 40,350 mg/l in the sixth steady state. The minimum solids retention time, which was obtained from the three kinetic models ranged from 6 to 14.4 days. The k values were in the range of and values were between 0.26 and 0.379 d-1. The solids retention time (SRT) decreased from 600 days to 14.3 days. The complete treatment reduced the COD content to 2279 mg/l equivalent to a reduction of 94.8% reduction from the original